Study of PVA-based nanocomposite polymer gels containing weak aliphatic dicarboxylic acids. Issue 3 (4th February 2020) - Kumar, Rajiv; Kaur, Simranpreet; Singh, Navneet; Sharma, Honey; Sharma, Shuchi
Abstract : In this study, nanocomposite polymer gel electrolytes have been prepared by using nanosize fumed silica (SiO2 ), poly(vinyl alcohol) (PVA), dimethyl sulfoxide (DMSO) and weak aliphatic acids (oxalic acid (OA), malonic acid (MA) and succinic acid (SA) with different dissociation constant values) and characterized by ionic conductivity, pH and viscosity studies. The ionic conductivity of liquid electrolytes has been found to depend on the dissociation constant values of the acids, which has been explained on the basis of the inductive effect. The decrease in the ionic conductivity of electrolytes observed with the addition of a polymer has been explained as being due to the increase in viscosity. The increase in the conductivity of gel electrolytes with the addition of nanofillers has been explained by using the double-percolation-threshold model. Maximum room-temperature conductivities of 2·12 × 10 −3, 7·3 × 10 −4 and 5·8 × 10 −4 S/cm have been obtained for nanocomposite gel electrolytes containing DMSO + 1 M OA, MA and SA + 10 wt% PVA at 6 wt% silica, respectively.